Analysis of Segmentation, Targeting, and Positioning in the Tourism Sector: The Case of Pekalongan City - Rilla Rianty; Maidar Simanihuruk; Alda Chairani; Budi Supriyanto; Rahmat Ingkadijaya (FIRM Journal of Management Studies, 2022)
Pekalongan is one of the largest batik-producing cities in Indonesia, and this potential can be used as an attraction to increase tourist visits. However, until now, the level of tourist visits in Pekalongan City has not met expectations. This study examines the tourism marketing strategy of Pekalongan City by using segmentation, targeting, and positioning (STP) variables to increase competition as a domestic and foreign tourist destination. The type of research used is field research with a qualitative approach. The study's results found that the leading geographical segment of Pekalongan City was domestic tourists from Central Java. The demographic is women with millennial characteristics ranging from 26 to 42 years old with business and group travel purposes. The type of tourists who visit Pekalongan City is only domestic tourists, meaning that marketers have not been able to penetrate international tourism. There is a contradiction between the research findings and the promise reflected in the slogan and logo of Pekalongan City tourism. The position of Pekalongan City as a batik city is not following the product that Pekalongan City excels in, namely religious tourism. Hence, the slogan of this city needs to be improved without ignoring batik as the primary differentiation.